2021
DOI: 10.1109/tasc.2021.3057327
|View full text |Cite
|
Sign up to set email alerts
|

Non-Thermal Absorption and Quantum Efficiency of SINIS Bolometer

Abstract: We study mechanisms of absorption in two essentially different types of superconductor-insulator-normal metalinsulator-superconductor (SINIS) bolometers with absorber directly placed on Si wafer and with absorber suspended above the substrate. The figure of merit for quantum photon absorption is quantum efficiency equal to the number of detected electrons for one photon. The efficiency of absorption is dramatically dependent on phonon losses to substrate and electrodes, and electron energy losses to electrodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…KID sensors are more robust, but require rather complicated readout electronics. As reported in [4], the SINIS parameters of responsivity dV/dP ∼ = 10 9 V/W and NEP < 10 −16 W/Hz 1/2 can be improved by using microwave superconducting quantum interferometer (SQUID) readout electronics. Integrating SINIS detectors in a series or parallel matrices [5,6] improves the dynamic range and allows for their use in ground-based observatories with a background power load of tens of picowatts.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…KID sensors are more robust, but require rather complicated readout electronics. As reported in [4], the SINIS parameters of responsivity dV/dP ∼ = 10 9 V/W and NEP < 10 −16 W/Hz 1/2 can be improved by using microwave superconducting quantum interferometer (SQUID) readout electronics. Integrating SINIS detectors in a series or parallel matrices [5,6] improves the dynamic range and allows for their use in ground-based observatories with a background power load of tens of picowatts.…”
Section: Introductionmentioning
confidence: 94%
“…The most sensitive of these are superconducting detectors cooled down to sub-kelvin temperatures, which are the part of an integrated quasi-optical receiving system. The main competitors are transitionedge sensors (TESs) [1], kinetic inductance detectors (KIDs) [2,3], and superconductorinsulator-normal metal-insulator-superconductor (SINIS) detectors [4]. The main advantage of a TES is its high sensitivity, and the drawbacks are a narrow dynamic range, low speed, and a requirement of temperature stability.…”
Section: Introductionmentioning
confidence: 99%
“…The development of quantum response theory [12] has made it possible to adequately describe processes at higher frequencies. A detailed experimental study of the transition from thermal absorption to quantum efficiency was carried out in [31] (schematic image of SINIS detector-see Figure 4). It was experimentally demonstrated that the thermal contact of the absorber and substrate could significantly reduce the responsivity.…”
Section: Quantum and Bolometric Responsementioning
confidence: 99%
“…The important conclusion drawn in [12,31] is that electron cooling does not lead to an increase in sensitivity. We analyzed the characteristic time constants of energy relaxation in different SINIS structures.…”
Section: Quantum and Bolometric Responsementioning
confidence: 99%
See 1 more Smart Citation